2021
DOI: 10.1051/e3sconf/202130603011
|View full text |Cite
|
Sign up to set email alerts
|

How does entrepreneurial orientation affect the business performance of coffee shop MSMEs in Indonesia?

Abstract: The increasing growth of the coffee shop business with a fast and attractive expansion as a food & beverage industry in urban areas of Indonesia, especially Special Region of Yogyakarta has led to business competition between micro, small, and medium enterprises (MSMEs) which are required to use their ability to adapt, be competitive and improve business performance. The entrepreneurial orientation is claimed to important contributions to business success. This study aims to analyze the effect of entrepren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
0
0
2
Order By: Relevance
“…Entrepreneurial approach has been associated with increased competitiveness in the setting of MSMEs (Hamdana et al, 2021;Santoso et al, 2020;Yeni, 2015). Research indicates that MSMEs with greater entrepreneurial orientation are better able to recognize and seize new possibilities, adjust to shifting market conditions, and outperform their less entrepreneurial peers (Ardhi & Mulyo, 2021;Perdana & Prasasti, 2023). Consequently, in order to develop strategies that fully utilize the inventive potential of MSMEs in Kintamani, it is essential to comprehend the relationship between entrepreneurial orientation and competitiveness.…”
Section: Entrepreneurial Orientation and Competitivenessmentioning
confidence: 99%
“…Entrepreneurial approach has been associated with increased competitiveness in the setting of MSMEs (Hamdana et al, 2021;Santoso et al, 2020;Yeni, 2015). Research indicates that MSMEs with greater entrepreneurial orientation are better able to recognize and seize new possibilities, adjust to shifting market conditions, and outperform their less entrepreneurial peers (Ardhi & Mulyo, 2021;Perdana & Prasasti, 2023). Consequently, in order to develop strategies that fully utilize the inventive potential of MSMEs in Kintamani, it is essential to comprehend the relationship between entrepreneurial orientation and competitiveness.…”
Section: Entrepreneurial Orientation and Competitivenessmentioning
confidence: 99%
“…Penelitian lain yang dilakukan oleh Ardhi et al (2021) yang bertujuan untuk menganalisis pengaruh orientasi kewirausahaan terhadap kinerja bisnis pada 80 pemilik UMKM di DI Yogyakarta menunjukkan bahwa dimensi proaktif, otonomi, dan agresivitas bersaing berpengaruh positif dan signifikan terhadap kinerja bisnis. Sedangkan dimensi inovatif dan pengambilan risiko tidak berpengaruh terhadap kinerja bisnis.…”
Section: Pendahuluanunclassified
“…Meningkatnya tren kopi dan penggunaan teknologi digital di Indonesia maka sangat memungkinkan bagi sebuah usaha meningkatkan kinerja bisnis dengan berinovasi melakukan pengembangan teknologi melalui aplikasi digital yang akan membantu kelancaran operasional usaha. Penelitian Sipayung et al (2021) dan Ardhi et al (2021) menunjukkan hasil yang berbeda dalam variabel inovasi pengembangan teknologi, di mana dalam penelitian Sipayung et al (2021) inovasi pengembangan teknologi berpengaruh positif terhadap kinerja bisnis sedangkan dalam penelitian Ardhi et al (2021) inovasi pengembangan teknologi tidak berpengaruh terhadap kinerja bisnis.…”
Section: Pendahuluanunclassified
“…These challenges are related to environmental sustainability and the value chain concept. Study [11], [12], [15] revealed the main challenge is the lack of awareness and knowledge of sustainable practices among coffee farmers and other stakeholders in the value chain in Kenya. This can lead to unsustainable agricultural practices, such as the use of harmful pesticides and fertilizers, which can negatively impact the environment and human health.…”
Section: Introductionmentioning
confidence: 99%